Management and engineering innovation - Machado, Carolina, 1965-; Davim, J. Paulo (London : ISTE ; Hoboken : Wiley, 2013)
This book discusses management and engineering innovation with a particular emphasis on human resource management (HRM) and production engineering. In an innovation context, the disciplines of management and engineering are linked to promote sustainable development, seeking cultural and geographical diversity in the studies of HRM and engineering, applications that can have a particular impact on organizational communications, change processes and work practices. This connection reflects the diversity of societal and infrastructural conditions.
4.6.1. Political and legal factors.
Includes bibliographical references and index.
Print version record.
Keywords: Technological innovations -- Management; Production engineering; Personnel management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Personnel management; Production engineering; Technological innovations -- Management; Electronic books; Electronic books